The Urgency of Doxing on Social Media Regulation and the Implementation of Right to Be Forgotten on Related Content for the Optimization of Data Privacy Protection in Indonesia - Sinta Dewi Rosadi; Enni Soerjati Priowirjanto; Teguh Cahya Yudiana (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
Data privacy that attached to every social media user has become a target of crime. One of the crime types that utilizes social media is doxing. Nowadays, the cases of doxing are increasing. There are still no specific and comprehensive normative rules that cover the data privacy protection to avoid doxing on social media. The fact makes the law enforcement still not optimal. This study is a descriptive study to answer some questions. Firstly, how to regulate doxing on social media based on the perspective of Indonesian law compared to the perspectives of other states in similar issue? Secondly, how the implementation of the right to be forgotten in doxing cases can optimize data privacy protection in Indonesia? This study used a normative juridical and case study approach. This study has resulted several results. Firstly, Indonesia needs special regulation for doxing on social media to protect the user data privacy. Secondly, the regulation of right to be forgotten should be reformulated and must be applied as a solution to doxing content. Doxing on social media regulation with the right to be forgotten can be further regulated through the legal regulation to provide a better data privacy protection.DOI: https://doi.org/10.22304/pjih.v9n1.a2